Research on the Numerical Simulation of the Nonlinear Dynamics of a Supercavitating Vehicle - Tianhong Xiong; Xianyi Li; Yipin Lv; Wenjun Yi (Shock and Vibration)
Little is known about the movement characteristics of the supercavitating vehicle navigating underwater. In this paper, based on a four-dimensional dynamical system of this vehicle, its complicated dynamical behaviors were analyzed in detail by numerical simulation, according to the phase trajectory diagram, the bifurcation diagram, and the Lyapunov exponential spectrum. The influence of control parameters (such as various cavitation numbers and fin deflection angles) on the movement characteristics of the supercavitating vehicle was mainly studied. When the system parameters vary, various complicated physical phenomena, such as Hopf bifurcation, periodic bifurcation, or chaos, can be observed. Most importantly, it was found that the parameter range of the vehicle in a stable movement state can be effectively determined by a two-dimensional bifurcation diagram and that the behavior of the vehicle in the supercavity can be controlled by selecting appropriate control parameters to ensure stable navigation.